Crossing the Creek : The Literary Friendship of Zora Neale Hurston and Marjorie Kinnan Rawlings - Lillios, Anna, 1948- (Book collections on Project MUSE., 2010)
Anna Lillios's 'Crossing the Creek' examines the productive and complex relationship between these two major figures. Is there truth to the story that Hurston offered to work as Rawlings's maid? Why did Rawlings host a tea for Hurston in St Augustine? Lillios examines these questions and many others.